Support Mission Task Force Kizi Konga XXXVII-H-Minusca at the UN Peace Mission in the Central African Republic - Elieser Ginting; Pujo Widodo; Bayu Setiawan (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to analyze the Support Mission of the Kizi Konga XXXVII-H/MINUSCA Task Force on Peace Missions in the Central African Republic. Using a descriptive qualitative approach and interviews as data collection methods, this study found that the implementation of support missions in Peace Missions in the Central African Republic were construction engineering, explosives disposal, and CIMIC.